The Crime Controversy: Avoiding Realities - Bazelon, David L. (1982)
Speaking before the nation's police chiefs last fall, President Reagan said, The frightening reality is that for all the speeches by those of us in Government-for all the surveys, studies, and blue ribbon panels--for all the 14-point programs and the declarations of war on crime--crime has continued its steady, upward climb and our citizens have grown more and more frustrated, frightened,and angry. 'I must concur with the President's depressing picture. In the thirty-two years that I have been on the bench, the war against crime has been a high national priority. Nevertheless, crime--and the fear of crime--seem worse today than ever before. Recent polls indicate that crime ranks right after world peace and economic issues in the concerns of Americans